2023
DOI: 10.1101/2023.12.22.23300455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“There is nothing that can prevent me from supporting her:” Men’s perspectives on their involvement and support of women’s use of topical therapy for cervical precancer treatment in Kenya

Chemtai Mungo,
Konyin Adewumi,
Everlyn Adoyo
et al.

Abstract: PurposeCervical cancer disproportionately impacts women in low- and middle-income countries (LMICs). The World Health Organization’s (WHO) 90/70/90 strategy aims to eliminate cervical cancer by 2030 by increasing HPV vaccination coverage to 90%, screening 70% of eligible women, and effectively treating 90% of those with abnormal results by 2030, potentially preventing 62 million deaths in LMICs. LMICs, however, struggle with limited access to cervical precancer treatment, in part due to a lack of trained profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In the cervical precancer treatment literature, studies have found that while guidelines recommend abstinence for 4-6 weeks after ablation or excisional procedures, 32 some women in Malawi, 39 Kenya, 40 and Peru 41 reported inability to maintain abstinence for the recommended period due to lack of male partner support. 38 Further studies, including pilot trials of self-administered topical therapies in LMICs, can investigate men's actual support of adherence recommendation, in contrast to the perceived support reported in our study. The shorter abstinence duration associated with topical therapies compared to conventional surgical precancer treatments may be an advantage for their use in these settings.…”
Section: Discussionmentioning
confidence: 60%
“…In the cervical precancer treatment literature, studies have found that while guidelines recommend abstinence for 4-6 weeks after ablation or excisional procedures, 32 some women in Malawi, 39 Kenya, 40 and Peru 41 reported inability to maintain abstinence for the recommended period due to lack of male partner support. 38 Further studies, including pilot trials of self-administered topical therapies in LMICs, can investigate men's actual support of adherence recommendation, in contrast to the perceived support reported in our study. The shorter abstinence duration associated with topical therapies compared to conventional surgical precancer treatments may be an advantage for their use in these settings.…”
Section: Discussionmentioning
confidence: 60%
“…41 Kisumu County is among the highest HIV burden regions in Kenya, with a 17.5% prevalence rate, compared to a national average prevalence of 4.9% in 2018. 42 Cervical cancer is the leading cause of cancer death for women in Kenya, with an estimated 3,200 deaths in 2020. 11…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a larger project exploring the acceptability of topical therapies for the treatment of HPV and cervical precancer, which included in-depth interviews and focus groups with women undergoing cervical cancer screening and male partners in Kenya, in eastern Africa. Results of a qualitative analysis of men's perspectives have been reported elsewhere [23]. This current analysis encompasses focus group discussions with female participants.…”
Section: Study Design and Approachmentioning
confidence: 99%
“…We used purposive sampling and a stepped recruitment process to recruit FGD participants, as described previously [23] [29]. Women age 25 to 65 years undergoing cervical cancer screening or precancer treatment in public clinics in western Kenya between November 2022 and April 2023 were included in the study.…”
Section: Sampling Recruitment and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation